Pengaruh Corporate Social Responsibility terhadap Tax Aggressiveness dengan Ukuran Perusahaan sebagai Variabel Moderasi - Dewi Kusuma Wardani; Ayu Pratiwi Wijayanti (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to determine the effect of corporate social responsibility on tax aggressiveness with firm size as moderation. The research method used is quantitative methods and secondary data using annual financial reports. The sample of this research is the property and real estate sector companies listed on the Indonesia Stock Exchange in 2016-2019. The results of this study indicate that corporate social responsibility has a positive effect on tax aggressiveness. Company size cannot moderate corporate social responsibility with tax aggressiveness. The conclusion of this study is that companies that disclose high CSR will have higher tax aggressiveness, because companies will attract public sympathy by disclosing broad CSR, to cover up the company's bad image with tax avoidance that has been carried out by the company. The existence of a large company size cannot affect the level of CSR disclosure. This is because large companies are not guaranteed to disclose broad CSR, where investors do not only look at how big the company is but also look at it from a financial perspective. Keywords: Corporate Social Responsibility, Tax Aggressiveness and Company Size